2001
DOI: 10.1034/j.1600-079x.2001.310401.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of extracellular calcium on the regulation of melatonin synthesis in the Syrian hamster pineal gland

Abstract: The role of extracellular calcium on the induction of cyclic AMP production, N-acetyltransferase (NAT) activity and melatonin synthesis, induced by forskolin, was investigated in Syrian hamster pineal glands. Pineals were removed from hamsters killed either in the first half of the normal dark period or late in the dark period. Forskolin immediately increased NAT activity and melatonin levels only when the glands were collected late in the dark period, while in the first half of the dark phase, hamster pineals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Note that other studies have found no significant effect of gender (e.g. Santana et al, 1991;Reiter, Reiter et al, 1994) or reproductive status (Reiter & Richardson, 1992;Zarazaga, Malpaux & Chemoneau, 1996). An explanation for this unusual finding warrants further investigation, particularly in light of the extensive reproductive skew in this eusocial mammal.…”
Section: Discussionmentioning
confidence: 98%
“…Note that other studies have found no significant effect of gender (e.g. Santana et al, 1991;Reiter, Reiter et al, 1994) or reproductive status (Reiter & Richardson, 1992;Zarazaga, Malpaux & Chemoneau, 1996). An explanation for this unusual finding warrants further investigation, particularly in light of the extensive reproductive skew in this eusocial mammal.…”
Section: Discussionmentioning
confidence: 98%
“…Pineal glands of the WT (n = 21; male n = 9, female n = 12) and Cry1 −/− /Cry2 −/− (n = 21; male n = 10, female n = 11) mice were sampled from mice kept in LD at ZT3 and individually incubated with 200 μL of DMEM at 37°C and 5% CO 2 for 30 min. After this pre-incubation, 200 μL of forskolin (FSK, final concentration, 50 μM) or vehicle (DMEM) was added to the culture medium at projected ZT3.5 and incubated at 37°C and 5% CO 2 for 1 h. The dose was reported to increase cAMP level and melatonin synthesis in cultured pineal gland (Santana et al 1988(Santana et al , 2001). The cultured pineal glands were rinsed by transferring them three times to new culture wells containing 200 μL of cold 0.1 M Tris-HCl buffer (pH 7.2).…”
Section: Cyclic Amp Content In the Pineal Gland After Treatment With mentioning
confidence: 99%
“…Viability of microspores in vivo varied with weather conditions and daylength (Tian et al 1998;Zeng et al 1999) and photoperiod-sensitive varieties of rice have been developed in which pollen aborts in the late microspore stage when exposed to long daylengths (Wu and Wang 1990). This loss of microspore viability has also been associated with an alteration in the concentration and distribution of calcium (Tian et al 1998;Poovaiah et al 1999), a key regulator of the rate-limiting enzyme in melatonin biosynthesis, N-acetyltransferase (Meissl et al 1996;Santana et al 2001). Our data show a decrease in serotonin and increase in melatonin corresponding to the transition from the tetrad to uninucleate microspore phases that may reflect an adaptation to changing photoperiod potentially through altered distribution of Ca 2+ .…”
Section: Discussionmentioning
confidence: 52%